Капітальні інвестиції за регіонами України: аналіз територіальної нерівності та часових коливань - Жерліцин, Д. М.; Мартинюк, Б. А.; Zherlitsyn, D. M.; Martyniuk, B. A. (Причорноморський науково-дослідний інститут економіки та інновацій, 2020)
Сталий розвиток економіки країни значною мірою визначається збалансованістю інвестиційного потенціалу її окремих регіонів та ефективністю регіональної політики. У статті визначено особливості територіального розподілу економічного потенціалу України на базі аналізу нерівномірності надходження капітальних інвестицій за регіональною та часовою ознаками. Авторами проведено узагальнення сучасних підходів до оцінювання показників соціально-економічного розвитку регіонів, уточнено сутність понять «інвестиційний потенціал» та «інвестиційні ризики розвитку територій». Визначено підходи до аналізу рівня нерівномірності територіального розподілу економічних ресурсів. Авторами розглянуто сальдо приросту обсягів капітальних інвестицій як ключовий індикатор зміни інвестиційного потенціалу областей України. Визначено області зі значним рівнем щоквартального приросту капітальних інвестицій та значними коливаннями цього показника.

The sustainable development of the country’s economy is significantly determined by the balance of the investment potential of its regions and the effec-tiveness of regional policy. The Ukrainian economy is determined by the significant territorial distribution of investment resources and the corresponding economic potential. Therefore, the purpose of the paper is to define the peculiarities of the territorial distribution of the economic potential of Ukraine based on the analysis of the unevenness of capital investment inflows by region and temporal characteristics. This article is based on the theoretical principles and methods of statistics and econometrics analysis; the system approach methods of defining the key indicators of the regional investment potential. The authors generalized modern approaches for assessing the indicators of social and economic development of regions clarified the concepts of “investment potential” and “investment risks of development of territories”. The approaches to the analysis of the level of uneven territorial distribution of economic resources are determined. The authors consider the growth of the balance of capital investment as a key indicator of changing the investment potential of Ukrainian regions. The paper determines the statistical characteristics of key regional investment indicator. The method of normal distributed random vari-able is applied to determinate the quarterly mean and variance of capital growth indicator by regions. The regions with values of the level of quarterly growth of capital investments and significant fluctuations of this indicator are determined. A comparative analysis of the quarterly dynamics of capital investment by regions in Ukraine proved the presence of 2 leading regions and 2 outsider regions. The authors prove that indicator of investment risk of the regions exceed the value of 0.3 for 10 out of 24 regions of Ukraine. Implementation of the results will increase the effects of the state regional policy of the Ukrainian economy. As a result, state and regional planning and control systems effectiveness will be improved.
Capital investments by regions of Ukraine: analysis of territorial inequality and time fluctuations
Keywords: регіон; інвестиційний потенціал; капітальні інвестиції; територіальна нерівність; часові коливання; region; investment potential; capital investment; territorial unevenness; temporal fluctuations